Project Management Skills in Green Construction Among Workers at Public Works Department (PWD) in The Construction Industry - Hassim, Hanis Maisarah; Shareh Musa, Sharifah Meryam; Kasim, Narimah; Mohd Noh, Hamidun; Zainal, Rozlin (Research in Management of Technology and Business, 2022)
Project management skills in green construction should be mastered by workers in the construction industry. There are several problems related to readiness in managing projects as well as lack of skills in handling green construction. To maintain the sustainability of construction, skills in the construction of green buildings are introduced to the whole world widely especially in the construction industry. The purpose of this study was to examine the skill needs and level of readiness in the management of green construction projects among employees in PWD Johor. The objectives of this study are as follows: determine the workers’ skills needed in green construction project management, determine the level of work readiness in green construction during the project management among the PWD workers, investigate steps taken by the PWD in ensuring green construction is carried out in Johor. The approach of this study is to use quantitative methods by distributing study questions to PWD workers consisting of engineers, assistant engineers, project managers, assistant project managers, site supervisors, assistant site supervisors, contractors. The overall response rate is 70% from 30 respondents and the data had been analyzed using IBM SPSS Software Version 26. From this research, the dominant skills from the respondents are transferable skills and the highest level of work readiness in managing a green construction project is project team-related. The most beneficial method used to ensure green construction was completed are to increase the use of green materials in a construction project.